Digital Marketing Adoption Among Small Businesses: A Case Study of Stamford University Graduates - Tutut Ruwaidah, Ari Trisna Winata, M. Zaidi Abdad (Lembaga Bale Literasi, 2025)
The swift development of digital technologies has transformed marketing practices worldwide, prompting small businesses to increasingly utilize digital platforms to strengthen their market presence, improve customer interaction, and enhance operational efficiency. This study explores the level and characteristics of digital marketing adoption among Stamford University graduates who run small businesses in Dhaka, Bangladesh. Employing a mixed-methods design, data were gathered through a structured questionnaire (n = 30) and in-depth semi-structured interviews (n = 10). The results offer insights into the types of tools employed, perceived advantages, implementation barriers, and the role of academic background in shaping digital marketing practices. The findings indicate that 83% of participants had adopted at least one form of digital marketing, with social media platforms particularly Facebook (90%) and Instagram (65%) being the most used. In contrast, more advanced tools such as SEO (28%), Google Ads (20%), and email marketing (15%) were used far less frequently. Although 76% of respondents reported improvements in customer reach and 69% experienced increased brand visibility, only 41% observed a meaningful rise in direct sales. Several challenges were identified, including limited technical expertise (reported by over 60% of participants), time constraints (45%), and insufficient understanding of return on investment. While respondents acknowledged that their education at Stamford University provided a solid theoretical grounding in business and marketing, 62% admitted that their practical digital marketing skills were largely developed independently. These findings point to a clear gap between academic instruction and practical application, emphasizing the need to incorporate hands-on digital literacy training into business curricula. Overall, this study contributes to the ongoing discussion on SME digital transformation in emerging economies and highlights the critical role of educational and institutional support in fostering effective digital marketing adoption.